Changes in pectin characteristics during the ripening of jujube fruit. (10th April 2017) - Ding, Shenghua; Wang, Rongrong; Shan, Yang; Li, Gaoyang; Ou, Shiyi
Abstract: BACKGROUND: Pectin is related to fruit maturation and loss of flesh firmness. In this research, changes in pectin characteristics, including pectin content, neutral sugar composition, molecular weight ( M w ) distribution and degree of methylesterification (DM), in six different growth stages (S1 to S6) of jujube fruit were assessed. RESULTS: The growth of jujube fruit corresponded to an increase in water‐soluble pectin (WSP) and a decrease in sodium carbonate‐soluble pectin (SSP). The chelate‐soluble pectin (CSP) content reached a maximum level at S3 but decreased significantly from S3 to S4. Arabinose proved to be the principal branched neutral monosaccharide in pectin during growth and was lost from WSP, CSP and SSP in S4 to S6. The ratios of (arabinose + galactose)/rhamnose indicated that the branched chains of WSP, CSP and SSP degraded in S2, S3 and S4 respectively. SSP depolymerized from S2 and increased as jujube fruit ripened. By contrast, WSP depolymerized throughout ripening. The DM of pectins ranged from 45.38 to 92.21%. Among the obtained DMs, the lowest was observed in WSP from ripened jujube fruit (S6). CONCLUSION: The content, neutral sugar composition, DM and M w distribution of pectins changed markedly as jujube fruit ripened. Jujube fruit could be a promising alternative source of pectins in terms of maturation degree. WSP from S6 and CSP from S1 or S2 could be used as gelling agents in low‐sugar‐containing products because of their low methoxyl pectin contents. WSP from S1 could also be applied as a thickener or emulsifier owing to its high M w distribution. © 2017 Society of Chemical Industry